Social Capital Wealth as a Predictor of Innovative Climate in Schools - Mahmut Polatcan; Ali Balcı (International Journal of Contemporary Educational Research, 2022)
This study aimed to investigate the relationship between social capital and innovative climate in secondary schools. Relational model was used in the research. 700 teachers from upper secondary schools were recruited through stratified sampling method. Data were collected through “Social Capital in Schools Scale” and “Innovative Climate in Schools Scale”. Mean, correlation and regression analyzes were used for data analysis. The results of the relationship between concepts revealed a positive high level of correlation between the social capital and the innovative climate in schools. Positive moderate and high significant relationships were found between the dimensions of social capital and the innovative climate of (except for openness to innovation). Finally, it was concluded that the social capital dimensions were a significant predictor of the innovative climate. Results were discussed within the scope of the development of social capital and innovative climate in schools.